PEREMPUAN JAWA: WACANA SAKRALITAS BATIK SOLO DALAM METAFISIKA - Naomi Kawasaki (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2012)
Abstrak: The term of â€œDiscourseâ€ which was defined by Foucult means that it creates the truth against the group of statements that belong to a single system of formation (episteme). Episteme is described as the certain structure of thought (knowledge) between the power relations that the man of a particularperiod cannot escape. In other word, discourse is the formation system of truth by the power of knowledge (a play of the truth). Batik Solo is a one of Javanese adhiluhung (high valued) cultures which is used as a traditional Javanese costume. Batik Solo was deeply connected to the Javanese womenâ€™sã€€whole life. It is not only a material things which protect human body but also spiritual things. Batik Solo is considered as a reflection of Javanese philosophical system, and expression of Javanese cosmology. Therefore it has sacred power which comes from outside of human world.For Javanese society, sacredness which is givenin Batik Solo, although in batik production proses by Javanese women and the way to use, is a truthof their life reality. In this point of view, Batik Solo can be said as a medium of visual communication which can be created the presence of Javanese women. The presence of women is not only a something â€œbeingâ€ but also â€œbeingsâ€,in other words it is a social construction historically. Thereby, in this article, it is strived that the metaphysics of Javanese womenâ€™s presence is broke up (read again/reinterpretation) in relation to Batik Solo. Kata Kunci: Diskursus, Sakralitas Batik Solo, Metafisika Kehadiran, Perempuan. Jawa